118k views
0 votes
If x = -10 and x + √7 - 7p = -3 solve for p

User Efleming
by
5.9k points

1 Answer

4 votes

Answer:

Hence, in the given expression, p = -0.6220

Explanation:

Here, the given expression is:

x = -10 and

x + √7 - 7 p = -3

Now, substitute x = -10 in the second equation, we get:

x + √7 - 7 p = -3 ⇒ -10 + √7 - 7 p = -3

Substituting √7 = 2.645751

Solving, it further, we get

-10 + √7 - 7 p = -3

-10 + 2.645751 + 3 = 7 p

or, -4.354248 = 7 p

or, p = -4.354248/7 = -0.6220

or, p = -0.6220

Hence, in the given expression, p = -0.6220

User Sanghyun Lee
by
6.8k points